Efficacy and Safety of an Autologous Micrografting Procedure for Management of Striae Distensae in Women - Leonor Girão; Pedro Pinto (Adis, Springer Healthcare, 2024)
Abstract Introduction Striae distensae (SD), or stretch marks, are a common skin problem having a psychological impact and cosmetic concern, especially for women, in whom the prevalence is higher than in men. This study assessed the efficacy and safety of a single autologous micrografting treatment (AMT®) using Rigenera® technology for the management of SD. Methods This single-centre study included 10 healthy women between 24 and 65 years of age, with Fitzpatrick-Goldman skin types I-IV, who had visible SD in glutes/thighs. Each subject acted as their own control. The treatment procedure (microneedling + AMT) and the control procedure (no treatment) were performed on contralateral sides of the glutes/thighs, targeting matched and paired SD. Microneedling was carried out using Dermapen®, equipped with 32 needle heads set at 1.5 mm needle length. The AMT procedure involved extracting biopsies from the mastoid hair zone with a 2.5-mm dermal punch, followed by disaggregation of the biopsies in a physiological saline solution using the Rigeneracons. The disaggregated micrografts were then intradermally injected using 30G 4-mm needles, maintaining a distance of 1 cm between injection points, covering the entire marked treatment region. Results In the treated area, at 3 months post-procedure compared to pre-procedure, the following changes were observed, all with statistical significance (P ≤ 0.05): (a) significant reductions in skin roughness (Ra, − 15.9%; Rz, − 22.6%), skin luminance (− 2.0%), and blue-green color distribution (− 10.6%); (b) significant increases in skin microcirculation maximum value (+ 240.1%), skin hydration (+ 71.2%), skin elasticity (+ 216.5%), skin density (+ 34.3%), skin thickness (+ 26.0%), and hypodermis thickness (+ 29.9%). Furthermore, for each of the aforementioned parameters, there was a significantly greater improvement observed with the AMT procedure compared with microneedling at 3 months (all P ≤ 0.05). Conclusion The AMT procedure using Rigenera technology resulted in an noticeable improvement in the SD appearance after 3 months in healthy women.